PELEVELAN PEMAHAMAN KONSEP KOMPOSISI FUNGSI BERDASAR TAKSONOMI SOLO (STRUCTURE OF OBSERVES LEARNING OUTCOMES) - Ulfa Lu’luatul Hidayah; Nur Rohman; Anita Dewi Utami (Journal of Mathematics Education and Science, 2020)
This qualitative descriptive study aims to describe the level of student understanding of function composition based on the SOLO taxonomy. This research was conducted at Madrasah Aliyah Islamiyah Balen on science class X students school year 2019/2020 with 20 subjects. Sampling using stratified sampling techniques (conditional sample) and purposive sampling (sample aims) see the results of written tests that refer to the grid of test questions and sampling data sources with specific considerations. Analysis of the level of understanding with PKLM1, PKLM2, PKLR1, PKLR2, PKLE1, and PKLE2. Data analysis using the test method and interview method and test the data's validity using the triangulation of data sources and triangulation of methods. The results showed three levels of students' understanding of the composition of functions based on SOLO taxonomy, namely multi structural, relational, and extended abstract. Penelitian deskriptif kualitatif ini bertujuan untuk mendeskripsikan level pemahaman siswa pada konsep komposisi fungsi berdasar taksonomi SOLO. Penelitian ini dilakukan di Madrasah Aliyah Islamiyah Balen pada siswa kelas X IPA tahun ajaran 2019/2020 dengan jumlah 20 siswa. Pengambilan sampel menggunakan teknik stratified sampling (sampel bersyarat) dan purposive sampling (sampel bertujuan) yaitu melihat hasil tes tulis yang mengacu pada kisi-kisi soal tes serta pengambilan sampel sumber data dengan pertimbangan tertentu. Analisis level pemahaman dengan subyek PKLM1, PKLM2, PKLR1, PKLR2, PKLE1, dan PKLE2. Analisis data menggunakan metode tes dan metode wawancara, serta uji keabsahan data menggunakan triangulasi sumber data dan triangulasi metode. Hasil penelitian menunjukkan ada tiga level pemahaman siswa pada konsep komposisi fungsi berdasar taksonomi SOLO yaitu multistruktural, relasional, dan extended abstract.